Comparing clinical features, severity and prognosis of autoimmune encephalitis and with and without oligoclonal bands - Xue, Hongfei; Guo, Xiaochan; Jiang, Yushu; Qin, Lingzhi; Wang, Xiaojuan; Xu, Jiajia; Zuo, Shaomin; Liu, Qiuyan; Li, Wei (Frontiers in Neurology, 2024)
This study aimed to examine the clinical distinctions among patients diagnosed with autoimmune encephalitis (AE) based on the presence or absence of cerebrospinal fluid (CSF) oligoclonal bands (OCBs). Additionally, it sought to explore the relationship between OCBs and the severity and prognosis of autoimmune encephalitis. Methods: A retrospective analysis was conducted on ninety-four patients diagnosed with AE at the People's Hospital of Zhengzhou University between October 2016 and June 2022. The patients were divided into OCB-positive and OCB-negative groups based on CSF-OCBs. Patient severity at admission was assessed utilizing the Clinical Assessment Scale for Autoimmune Encephalitis (CASE) and the modified Rankin Scale (mRS). Additionally, some oligoclonal-positive patients underwent dynamic longitudinal analysis of cerebrospinal fluid test indices. The mRS score was ultimately employed to evaluate patients' short-term prognosis (6 months) and long-term prognosis (at least 12 months) following immunotherapy. Results: Of the 94 patients, 34 (36.2%) belonged to the OCB-positive group, while 60 (63.8%) belonged to the OCB-negative group. The group with anti-n-methyl-d-aspartate receptor (anti-NMDAR) encephalitis exhibited the highest rate of oligoclonal positivity at 27 (49.1%), followed by anti-aminobutyric acid B receptor (GABABR) encephalitis with 4 cases (30.8%), anti-contactin-associated protein-like 2 (CASPR2) encephalitis with 2 cases (20%), and anti-leucine-rich glioma inactivating protein 1 (LGI1) encephalitis with 1 case (6.25%).The OCB-positive group exhibited higher rates of autonomic dysfunction, intensive care unit (ICU) admission, CSF leukocytes, and IgG index compared to the OCB negative group (p<0.05). Additionally, the OCB-positive group had significantly higher median CASE and mRS scores prior to immunotherapy than the OCB-negative group (p<0.001; p<0.001).Furthermore, in both short-term follow-up and long-term follow-up, the OCB-positive group had a significantly lower proportion of patients with a favorable prognosis compared to the OCB-negative group (50% vs 71.7%, 61.8% vs 83.3%; p=0.036, p=0.002).: Autonomic dysfunction, ICU admission, leukocytes in the cerebrospinal fluid, and elevated IgG index are more commonly observed in OCB-positive patients. OCB-positivity has also been linked to the severity and prognosis of AE, making it a potential biomarker. Initial OCB testing aids clinicians in identifying potentially critically ill patients early and monitoring disease progression, thereby optimizing clinical treatment decisions.